Variations of dissolved organic matter and Cu fractions in rhizosphere soil induced by the root activities of castor bean. (September 2020) - Huang, Guoyong; Zhou, Xiupei; Guo, Guagguang; Ren, Chao; Rizwan, Muhammad Shahid; Islam, Md Shoffikul; Hu, Hongqing
Abstract: The root soil interaction affects metal bioavailability in the rhizosphere, thus impacting the uptake and accumulation of metals by plants. In this study, a greenhouse experiment using a root-bag technique for castor bean plants was conducted to determine the i) rhizosphere effect on the fractions of Cu, and ii) the characteristics of dissolved organic matter (DOM) in the rhizosphere soil. Results showed that the Cu concentration in the leaves, stems, and roots was 15.41, 6.71, and 47.85 mg kg −1, respectively, in the control and reached up to 96.5, 254.9, and 3204 mg kg −1 in Cu400 treatment, respectively. After cultivating castor bean plants, the concentration of acid exchangeable Cu in rhizosphere soil was higher than that in the bulk soil for the same Cu addition, whereas the concentrations of reducible Cu, oxidizable Cu, and residual Cu in the rhizosphere soil were all lower than those in the bulk soil, respectively. In comparison to the bulk soil, the pH decreased while the total nitrogen and total carbon concentrations both increased in the rhizosphere soil. Moreover, the concentrations of total low molecular weight organic acids (LMWOAs) and total amino acids in the rhizosphere soil of the Cu treatments increased by between 15.18% to 47.17% and 36.35%–200%, respectively with respect to the control. The less complex DOM with a high LMWOAs concentration in the rhizosphere soil shifted the soil Cu from a relative stable fraction to available fractions. Graphical abstract: Image 1 Highlights: Rhizosphere soil pH was lower than that of bulk soil. Higher contents of TC and TN but less complex structure of DOM was observed in rhizosphere soil than that of bulk soil. LMWOAs and amino acids were the main compositions of DOM from rhizosphere soil. Root activates of castor bean induced the transformation of Cu fractions in rhizosphere soil.